Prevalence of diabetic dyslipidaemia in younger age group - Sarkar, Susmita; Dawn, Indranil (Bangladesh Journal of Medical Science, 2017)
Background: The commonest cause of mortality & morbidity in Type 2 diabetes is cerebrovascular accident & coronary artery disease. The study shows that only good blood glucose control, along with BP control in Type 2 diabetic patients cannot reduce mortality & morbidity due to cerebrovascular accident & coronary artery disease; but dyslipidaemia & life style modification is the cornerstone to reduce mortality & morbidity for those events. Dyslipidaemia in diabetes mellitus is a common accompaniment. Prevalence of lipid profile abnormality may not uncommon in young Type 2 diabetics which is common in elderly Type 2 diabetic patients. Aims: The aim of the study is to look after the prevalence of dyslipidaemia in younger age group & to compare it with elderly age group with the same anthropometric parameters. Methodolgy: A prospective cohort study was undertaken to find out the prevalence of diabetic dyslipidemia in younger and adult age group among patients attending Medical OPD & Diabetic clinic in M.G.M. Medical college &L.S.K. Hospital, Kishanganj, Bihar& to compare it between young and adult age group. Results: In the present study majority of patients of older age group have high LDL and low HDL in comparison to younger age group. Increased triglyceride level is not significantly high. Conclusion: Aggressive therapy of diabetic dyslipidemia will probably reduce the risk of CHD in patients with diabetes. Primary therapy should be directed first at lowering LDL levels & improving HDL levels. Bangladesh Journal of Medical Science Vol.16(4) 2017 p.557-563